Blue‐light filtering intraocular lenses (IOLs) for protecting macular health - Downie, Laura E (Cochrane Database Syst Rev, 2018)
BACKGROUND: An intraocular lens (IOL) is a synthetic lens that is surgically implanted within the eye following removal of the crystalline lens, during cataract surgery. While all modern IOLs attenuate the transmission of ultra‐violet (UV) light, some IOLs, called blue‐blocking or blue‐light filtering IOLs, also reduce short‐wavelength visible light transmission. The rationale for blue‐light filtering IOLs derives primarily from cell culture and animal studies, which suggest that short‐wavelength visible light can induce retinal photoxicity. Blue‐light filtering IOLs have been suggested to impart retinal protection and potentially prevent the development and progression of age‐related macular degeneration (AMD). We sought to investigate the evidence relating to these suggested benefits of blue‐light filtering IOLs, and to consider any potential adverse effects. OBJECTIVES: To assess the effects of blue‐light filtering IOLs compared with non‐blue‐light filtering IOLs, with respect to providing protection to macular health and function. SEARCH METHODS: We searched the Cochrane Central Register of Controlled Trials (CENTRAL) (which contains the Cochrane Eyes and Vision Trials Register) (2017, Issue 9); Ovid MEDLINE; Ovid Embase; LILACS; the ISRCTN registry; ClinicalTrials.gov and the ICTRP. The date of the search was 25 October 2017. SELECTION CRITERIA: We included randomised controlled trials (RCTs), involving adult participants undergoing cataract extraction, where a blue‐light filtering IOL was compared with an equivalent non‐blue‐light filtering IOL. DATA COLLECTION AND ANALYSIS: The prespecified primary outcome was the change in distance best‐corrected visual acuity (BCVA), as a continuous outcome, between baseline and 12 months of follow‐up. Prespecified secondary outcomes included postoperative contrast sensitivity, colour discrimination, macular pigment optical density (MPOD), proportion of eyes with a pathological finding at the macula (including, but not limited to the development or progression of AMD, or both), daytime alertness, reaction time and patient satisfaction. We evaluated findings related to ocular and systemic adverse effects. Two review authors independently screened abstracts and full‐text articles, extracted data from eligible RCTs and judged the risk of bias using the Cochrane tool. We reached a consensus on any disagreements by discussion. Where appropriate, we pooled data relating to outcomes and used random‐effects or fixed‐effect models for the meta‐analyses. We summarised the overall certainty of the evidence using GRADE. MAIN RESULTS: We included 51 RCTs from 17 different countries, although most studies either did not report relevant outcomes, or provided data in a format that could not be extracted. Together, the included studies considered the outcomes of IOL implantation in over 5000 eyes. The number of participants ranged from 13 to 300, and the follow‐up period ranged from one month to five years. Only two of the studies had a trial registry record and no studies referred to a published protocol. We did not judge any of the studies to have a low risk of bias in all seven domains. We judged approximately two‐thirds of the studies to have a high risk of bias in domains relating to ‘blinding of participants and personnel' (performance bias) and ‘blinding of outcome assessment' (detection bias). We found with moderate certainty, that distance BCVA with a blue‐light filtering IOL, at six to 18 months postoperatively, and measured in logMAR, was not clearly different to distance BCVA with a non‐blue‐light filtering IOL (mean difference (MD) ‐0.01 logMAR, 95% confidence interval (CI) ‐0.03 to 0.02, P = 0.48; 2 studies, 131 eyes). There was very low‐certainty evidence relating to any potential inter‐intervention difference for the proportion of eyes that developed late‐stage AMD at three years of follow‐up, or any stage of AMD at one year of follow‐up, as data derived from one trial and two trials respectively, and there were no events in either IOL intervention group, for either outcome. There was very low‐certainty evidence for the outcome for the proportion of participants who lost 15 or more letters of distance BCVA at six months of follow‐up; two trials that considered a total of 63 eyes reported no events, in either IOL intervention group. There were no relevant, combinable data available for outcomes relating to the effect on contrast sensitivity at six months, the proportion of eyes with a measurable loss of colour discrimination from baseline at six months, or the proportion of participants with adverse events with a probable causal link with the study interventions after six months. We were unable to draw reliable conclusions on the relative equivalence or superiority of blue‐light filtering IOLs versus non‐blue‐light filtering IOLs in relation to longer‐term effects on macular health. We were also not able to determine with any certainty whether blue‐light filtering IOLs have any significant effects on MPOD, contrast sensitivity, colour discrimination, daytime alertness, reaction time or patient satisfaction, relative to non‐blue‐light filtering IOLs. AUTHORS' CONCLUSIONS: This systematic review shows with moderate certainty that there is no clinically meaningful difference in short‐term BCVA with the two types of IOLs. Further, based upon available data, these findings suggest that there is no clinically meaningful difference in short‐term contrast sensitivity with the two interventions, although there was a low level of certainty for this outcome due to a small number of included studies and their inherent risk of bias. Based upon current, best‐available research evidence, it is unclear whether blue‐light filtering IOLs preserve macular health or alter risks associated with the development and progression of AMD, or both. Further research is required to fully understand the effects of blue‐light filtering IOLs for providing protection to macular health and function.